Legal Aspects of The Process of Forming A State-Owned Enterprise Holding Company Industrial Estate Cluster - Alfiani, Amiroh; Deviany, Oky; Wahyuni, Andi Suci (Hasanuddin Civil and Bussiness Law Review, 2024)
This research aims to analyze the suitability of the process of transferring government shares into PT Danareksa (Persero) shares with statutory provisions and analyze the protection of the rights of minority shareholders in the process of holding company PT Danareksa (Persero). This type of research uses normative legal research with a statutory approach and conceptual approach. The statutory approach is carried out by examining legislation or statutory studies. The conceptual approach is carried out in order to find the process and mechanism of holding SOEs. Analysis of legal materials is carried out using content analysis. The results of this study, namely: 1) The transfer of government shares into shares of PT Danareksa (Persero) is carried out with PP 72/2016, but the implementation of the provisions in PP 72/2016 related to state equity participation does not correspond to the arrangements in state finances regarding the formation of holding companies and also on the status of State Owned Enterprises (SOE). The absence of arrangements regarding the mechanism for implementing the holding provides different implementation practices. There is a practice of forming virtual holding in the pre-implementation stage. In the post-holding implementation, the status of subsidiaries in BUMN holding companies is still treated like SOE; 2) Legal protection in the holding process carried out by the Ministry of SOEs together with PT Danareksa (Persero) has not paid attention to the rights of minority shareholders, in this case the Provincial / City Government, although it is clearly regulated in the 2007 Company Law that minority shareholders should also be involved. In the holding process, it is important for the Ministry to fulfill the rights of minority shareholders, especially in each stage of the holding.